Literacy development and education in multiage k-4 classrooms - Juska-Bacher, Britta; Bertschi Kaufmann, Andrea; Knechtel, Nora; Schneider, Hansjakob (Swiss Journal of Educational Research, 2018)
One of the aims of the multiage elementary classroom model is the improvement of children’s literacy learning, a key area of instruction in the early school years. However, little is known about the practices of reading and writing education in multiage classrooms. This issue is addressed by the longitudinal study «Fostering literacy development in multiage elementary classrooms». Using one multiage classroom as an example, our article demonstrates how heterogeneous the prerequisites of the pupils are and how the teacher attempts to meet their individual needs and interests. The teacher’s self-reported instructional practices can be described by a high degree of individualized instruction and by a strong focus on multiage learning arrangements that are supportive for all participants. Finally, the teacher combines more age-group- with more domain-oriented approaches in order to integrate kindergarten and elementary styles of schooling.